Identificação do potencial para a gestão compartilhada, particular e pública, de unidades de conservação - May, Dayane (2015)
This shared management proposal aims to optimize the conservation and encourage environmental education (EA) through partnerships between the public sphere of the Parque Estadual (PE) do Monge and the private sphere of the Reserva Particular do Patrimônio Natural (RPPN) Uru, located in the Lapa municipality, PR. The areas represent an important remnant of the Araucaria Forest and Natural Grassland in Paraná. The established partnerships will allow the development of conservation policies, promotion of programs, action plans, research projects and EA, in order to maintain environmental quality. The proposed methodology was divided into three phases. The first consisted on the elaboration of an environmental diagnosis of the main components of the RPPN Uru and PE Monge, in relation to the biotic, physical and anthropic ways, to identify the fragments of the conservation status. In the second phase a proposal was presented for socio-environmental intervention at RPPN Uru. From the diagnosis and socio-environmental intervention proposal, the third phase included the proposal for shared management, as well as the intervention in protected areas, consisted of three stages: diagnosis, planning and monitoring. A análise dos componentes físico, biótico e antrópico da RPPN Uru e PE do Monge ampliou o conhecimento acerca dos processos ecológicos presentes nos ecossistemas naturais e dos aspectos sociais do município da Lapa. The survey of the physical environment identified the predominantly sandstone soil, with gentle topography and rich hydrographic system, factors that show the susceptibility of these protected areas to anthropic pressures. In studies of the biotic environments (flora and fauna), the floristic survey determined 572 species belonging to 101 families. In the research of the fauna, 31 species were identified, 25 of which are included in the “Livro Vermelho da Fauna Ameaçada no Estado do Paraná”, i.e., threatened. The region of RPPN Uru and PE Monge, characterized in the anthropic environment, was represented primarily by two different scenarios: an urban, with the influence of the city of Lapa, and another with rural nature, with agriculture, pasture and reforestation. As a consequence, conflicting situations were observed, resulting in the environmental action proposal, which focus on environmental education. Finally, the shared management proposal of RPPN Uru and PE do Monge established was to plan actions through knowledge lines (environmental research and education), control (supervision and protection), operation (administration, communication and economic sustainability), as well as the monitoring of indicators obtained from the suggested actions, which is the third stage, in order to make the necessary adjustments and innovations, and also propose further action. It is expected the establishment of shared management through the mobilization of the government agencies in the implementation of policies, action plans and projects of research and environmental education. The management of the connectivity between the two areas represents the enhancement of conservation actions and the encouragement of EA, resulting in the maintenance of ecosystems and the sustainable use of natural resources.